PENGEMBANGAN MEDIA GAMBAR MENGGUNAKAN APLIKASI MOVIE MAKER PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN UNTUK KELAS VIII SMP - Hadesti, Dini - (Pendidikan Biologi, 2014)
Education has important role to guarantee the development of a nation, because education is a process studying and teaching which is happened responses interaction between teacher and student thatâs located in school. The aim of this research is to produce picture media that used movie maker application in material structural and issue functional of plantation which hasnât been done in SMPN 1 Sungai Limau Kabupaten Padang Pariaman. Because of that, itâs done the research about picture media developing which purposes to produce valid and practice picture media. This research is developing research which is used 3 steps of 4-D model (define, design, and develop). The subjects of this research 4 validator (2 biology lectures and 2 biology teacher), and also 20 students of SMP 1 Kabupaten Padang Pariaman. The data research is premier data which is gotten from validity and practicality questionnaire. From the research produces like picture media using movie maker application with validity value 91,69% which is stated as very valid by validator, whether from content, construction, and language. Picture media movie maker which is produced has practicality value 95% and 97,06% by the student which is mean that itâs very practice, from student interest side in use process, student and time activation. From that result, it can be concluded that picture media use movie make application which is produced has been valid and very practice.